Factors affecting museum buildings and heritage spaces in terms of energy optimization and comfort - Mohamed Mostafa Refat Ismail; Ashraf Aly Nessim; Fatma Fathy (Ain Shams Engineering Journal)
Museum buildings host a special environment that is complex in its nature and could not be simplified in a single set of requirements, such as lighting challenges, energy consumption and visitor comfort. Mismanaging that could damage or affect the aging of sensitive objects and deprive the museum’s light and thermal comfort. Finding the balance of environmental comfort for the artifacts and the visitor simultaneously is always challenging in which most cases prioritized either one over the other. Consequently, this created a gap was created in the museum building and energy industry. The paper aims at identifying architectural design to help reduce energy costs and optimize smart systems efficiency in thermal and daylight while achieving high functionality. Here, the study elaborates the problem through analyzing multiple case studies and evaluating factors affecting energy and daylighting efficiency.After comparing 50 case studies according to six main factors in the building, architectural intervention techniques and MEP techniques are the most applicable and effective in museums indoor environment. In conclusion, mass design and envelope techniques are identified as the most impactful factors in architectural interventions for optimizing energy consumption and regulation, as evidenced by multiple case studies. Based on construction methods and climate-based classifications, observations showed that cold weather museums prefer envelope techniques, average climates use both equally with a preference for atriums, and hot climates predominantly use shading by mass. Renovated museums focus on MEP improvements, while new constructions have broader options. These insights guide the optimal architectural application for the base model, considering factors like floor mass dimensions, vertical shifts, shading devices and window-to-wall ratios, while keeping materials constant and excluding renewable resources and MEP solutions.